2022
DOI: 10.3389/fonc.2022.779621
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intraoperative Neural Tunnel in Protecting Recurrent Laryngeal Nerve: Experiences in Open, Trans Breast, and Transoral Endoscopic Thyroidectomy

Abstract: BackgroundEnergy-based devices (EBDs) increase the risks of thermal nerve injuries. This study aimed to introduce a surgical strategy of intraoperative neural tunnel protecting (INTP) for evaluating the effect in reducing the incidence of recurrent laryngeal nerve (RLN) damage in open, trans breast, and transoral endoscopic thyroidectomy.MethodsINTP strategy was introduced: a tunnel was established and protected by endoscopic gauze along the direction of the nerve. A total of 165, 94, and 200 patients with pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
(28 reference statements)
1
5
0
Order By: Relevance
“… 9 IONM allows easier identification, dissection, and preservation of the RLN during ET‐BA. 6 , 10 , 11 However, our study confirmed that RLN injury can still occur, even when using IONM. Separation, transection, and thermal RLN injuries were most common.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“… 9 IONM allows easier identification, dissection, and preservation of the RLN during ET‐BA. 6 , 10 , 11 However, our study confirmed that RLN injury can still occur, even when using IONM. Separation, transection, and thermal RLN injuries were most common.…”
Section: Discussionsupporting
confidence: 65%
“…Surgeons who perform ET must be able to identify, dissect, and expose the RLN using endoscopic instruments and view 9 . IONM allows easier identification, dissection, and preservation of the RLN during ET‐BA 6,10,11 . However, our study confirmed that RLN injury can still occur, even when using IONM.…”
Section: Discussionmentioning
confidence: 50%
“…Protection of the RLN and parathyroid gland is particularly important in thyroid surgery, as this directly affects the patient’s quality of life 32 . In this study, there was no statistically significant difference in the incidence of injury to the RLN and parathyroid gland between the two groups.…”
Section: Discussionmentioning
confidence: 45%
“…Protection of the RLN and parathyroid gland is particularly important in thyroid surgery, as this directly affects the patient's quality of life. 32 In this study, there was no statistically significant difference in the incidence of injury to the RLN and parathyroid gland between the two groups. Apart from the operator's familiarity with the anatomic location, the magnifying effect of the endoscope also helped the surgeon better identify the RLN and parathyroid gland, thus providing better protection.…”
Section: Discussionmentioning
confidence: 49%
“…The Thyroid Cancer-Specific Quality of Life Questionnaire (THYCA-QOL) has highlighted concerns with scarring, and a history of minimally invasive thyroid surgery was found to be associated with better thyroid cancer-specific QOL (3). In the pursuit of improved cosmetic outcomes, various endoscopic thyroid surgery approaches have been introduced, with the bilateral areolar approach showing promise and being particularly recommended for lymph node dissection (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%